2003
DOI: 10.1073/pnas.1036825100
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric speciation through intraspecific social parasitism

Abstract: Sympatric speciation through intraspecific social parasitism has been proposed for the evolution of Hymenopteran workerless parasites. Such inquilines exploit related host taxa to produce their own sexual offspring. The relatedness of inquilines to their hosts has been generalized in Emery's rule, suggesting that social parasites are close or the closest relatives to their host species. If the closest relative of each parasite is its host, then multiple independent origins of the parasite species are implied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 58 publications
5
119
3
2
Order By: Relevance
“…This result is not forgone, because polymorphism loss could proceed in directions not consistent with morphic speciation, such as by losing all throat colors or by a new throat color type evolving that excluded all others. Prior evidence for morphic speciation has largely consisted of monomorphic species resembling a morph found in a closely related polymorphic species (2,6,10). We also found that morph loss was coincident with species formation, because two of the four subspecies we sampled were monomorphic and the one insular species sampled was dimorphic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not forgone, because polymorphism loss could proceed in directions not consistent with morphic speciation, such as by losing all throat colors or by a new throat color type evolving that excluded all others. Prior evidence for morphic speciation has largely consisted of monomorphic species resembling a morph found in a closely related polymorphic species (2,6,10). We also found that morph loss was coincident with species formation, because two of the four subspecies we sampled were monomorphic and the one insular species sampled was dimorphic.…”
Section: Discussionmentioning
confidence: 99%
“…Tests of how polymorphisms diversify into new lineages have been relatively rare (2,5,6), despite increasing recognition that polymorphisms, such as alternative mating strategies, are common within species (7)(8)(9). Here we investigate the processes by which a morph in a polymorphic population may diverge to found a new species.…”
mentioning
confidence: 99%
“…The recent research on the phylogenetic relationships of social parasites with their hosts has produced many different results, some seeming to show strong support for sympatric speciation (Savolainen and Vepsäläinen, 2003;Sumner et al, 2004), while others appear to provide evidence against a sympatric origin of social parasites (Carpenter et al, 1993;Choudhary et al, 1994;Ward, 1996;Steiner et al, 2006). It may very well be that the different relationships obtained are due to the different divergence dates of the parasitic species used in each of these studies.…”
Section: Discussionmentioning
confidence: 63%
“…This range in the degree of adaptation to social parasitism is reflected in taxonomic structure, with some parasites accorded generic status, and others being placed in the same genus as their hosts. It seems likely that the extent of morphological adaptation to a parasitic lifestyle is at least partly correlated with the length of time since parasitism evolved (Savolainen and Vepsäläinen, 2003) and, if so, suggests a wide variation in the age of these parasitic allodapine lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The most spectacular example of ongoing parasitic speciation processes within the genus Myrmica is that of M. rubra and its microgyne form, the so-called M. microrubra (Savolainen and Vepsäläinen, 2003). The small queens of M. rubra are results of an isometric reduction in normalsized queens called macrogynes and they have the same negative queen effect on the development of overwintering larvae as 'normal' queens have (Elmes, 1976).…”
Section: Arnaldomentioning
confidence: 99%